2022
DOI: 10.1503/cmaj.220068
|View full text |Cite
|
Sign up to set email alerts
|

Association between long-term exposure to ambient air pollution and COVID-19 severity: a prospective cohort study

Abstract: Background: The tremendous global health burden related to COVID-19 means that identifying determinants of COVID-19 severity is important for prevention and intervention. We aimed to explore long-term exposure to ambient air pollution as a potential contributor to COVID-19 severity, given its known impact on the respiratory system. Methods: We used a cohort of all people with confirmed SARS-CoV-2 infection, aged 20 years and older and not residing in a long-term care fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Of the remaining studies, all but Chen, Wang et al (26) found a significant positive association between PM 2.5 and COVID-19 mortality. Chen, Sidell et al (37) found that PM 2.5 was consistently associated with higher mortality rates across multiple models, regardless of whether PM 2.5 was measured in the previous month or year and whether the model adjusted for NO 2 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the remaining studies, all but Chen, Wang et al (26) found a significant positive association between PM 2.5 and COVID-19 mortality. Chen, Sidell et al (37) found that PM 2.5 was consistently associated with higher mortality rates across multiple models, regardless of whether PM 2.5 was measured in the previous month or year and whether the model adjusted for NO 2 .…”
Section: Resultsmentioning
confidence: 96%
“…There was no evidence of publication bias ( p = 0.100). Trim-and-fill points could not be applied, though leave-one-out sensitivity analysis indicated the results remained positive but only became significant with the exclusion of Chen, Wang et al (26) (OR: 1.66; 95% CI: 1.06 to 2.59). These results are summarised in Supplementary Figures 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, no association between air pollutants and SARS-CoV-2 positive testing was detected in the COVICAT cohort of Catalonia, Spain, although a statistically significant association was estimated with severe COVID-19 disease among infected patients [8]. No association between PM 2.5 or NO 2 and mortality was found in a prospective longitudinal study conducted in Ontario, Canada, while significant associations were estimated with hospitalizations and accesses to intensive care units [9]. In contrast, positive associations between PM 2.5 exposure and COVID-19 incidence were estimated in northern Italy [10] and southern California [11].…”
mentioning
confidence: 99%
“…Estimates were smaller for NO 2 . ( Chen et al., 2022a ) Jiangsu province, China PM 2.5 , PM 10 Increased risk of severe COVID-19 with OR of 3.99 (1.93-8.25) and 1.82 (1.35-2.44) was associated with a unit increase in PM 2.5 and PM 10 . ( Li et al., 2022 ) Varese, Italy PM 2.5 , PM 10 , NO 2 , NO A unit increase in PM 2.5 was associated with a 5.1% (2.7%-7.5%) increase in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%